You can put this solution on YOUR website!
(f-g)(x)=f(x)-g(x) for all x.
For x=2 (f-g)(2)=f(2)-g(2)
You have 2 options to solve your problem:
Option 1 _ You can first work with the x in the functions as they are written to generate the general expression for (f-g)(x), and substitute x=2 later.
Option 2 _ You can calculate f(2) and g(2) first and then do the subtraction with the two numbers.
All that's said above works similarly for (f+g), (fxg) and (f/g)
Sometimes one option is easier or more convenient than the other.
In your case: